The Association Among Hypogonadism, Symptom Burden, and Survival in Male Patients with Advanced Cancer - Dev, R (2014)
BACKGROUND: A high frequency of hypogonadism has been reported in male patients with advanced cancer. OBJECTIVES: To evaluate the association among low testosterone, symptom burden and survival in cancer patients. METHODS: 119/131 (91%) consecutive male cancer patients had an endocrine evaluation of total/free/bioavailable testosterone (TT, FT, BT, respectively), high-sensitivity C-reactive protein (CRP), vitamin B12, thyroid stimulating hormone, 25-hydroxy vitamin D and cortisol levels when presenting with symptoms of fatigue and/or anorexia-cachexia. Symptoms were evaluated by the Edmonton Symptom Assessment Scale. We examined the correlation with Spearman test and survival with log rank test and Cox-regression analysis. RESULTS: The median age was 64; majority were white 85 (71%). Median TT was 209ng/dL (normal ≥200 ng/dL), FT was 4.4 ng/dL (normal ≥9 ng/dL), and BT was 22.0 ng/dL (normal ≥61ng/dL). Low TT, FT, and BT values were all associated with worse fatigue (p≤0.04), poor performance status (p≤0.05), weight loss (p≤0.01), and opioid use (p≤0.005). Low TT and FT were associated with increased anxiety (p≤0.04), decreased feeling of well-being (p≤0.04), and increased dyspnea (p≤0.05); while BT was only associated with anorexia (p=0.05). Decreased TT, FT, and BT values were all significantly associated with elevated CRP, low albumin and hemoglobin. In multivariate analysis, decreased survival was associated with low TT (HR 1.66; p=0.034), declining ECOG performance status (HR 1.55; p=0.004), high CRP (HR 3.28; p<0.001), and decreased albumin (HR 2.52; p<0.001). CONCLUSION: In male cancer patients, low testosterone was associated with systemic inflammation, weight loss, increased symptom burden, and decreased survival.